The skull of Monolophosaurus jiangi (Dinosauria: Theropoda) and its implications for early theropod phylogeny and evolution - Brusatte, S; Benson, R; Currie, P; Xijin, Z (2010)
The Middle Jurassic was a critical time in the evolution of theropod dinosaurs, highlighted by the origination and initial radiation of the large-bodied and morphologically diverse Tetanurae. Middle Jurassic tetanurans are rare, but have been described from Europe, South America and China. In particular, China has yielded a number of potential basal tetanurans, but these have received little detailed treatment in the literature. Chief among these is Monolophosaurus jiangi, known from a single skeleton that includes a nearly complete and well-preserved skull characterized by a bizarre cranial crest. Here, we redescribe the skull of Monolophosaurus, which is one of the most complete basal tetanuran skulls known and the only quality source of cranial data for Middle Jurassic Chinese theropods. The cranial crest is atomized into a number of autapomorphic features and several characters confirm the tetanuran affinities of Monolophosaurus. However, several features suggest a basal position within Tetanurae, which contrasts with most published cladistic analyses, which place Monolophosaurus within the more derived Allosauroidea. Cranial characters previously used to diagnose Allosauroidea are reviewed and most are found to have a much wider distribution among Theropoda, eroding an allosauroid position for Monolophosaurus and questioning allosauroid monophyly. The use of phylogenetic characters relating to theropod cranial crests is discussed and a protocol for future use is given. The systematic position of Guanlong wucaii is reviewed, and a basal tyrannosauroid affinity is upheld contrary to one suggestion of a close relationship between this taxon and Monolophosaurus. © 2010 The Linnean Society of London.